Parental Engagement in Schooling: A Survey of Secondary Schools in Kwara State, Nigeria - Martins Olanrewaju Atunde; Abdulganiyu Tijani; Johnson Medupin; Ijeoma Ogbudinkpa; Janet Oladejobi (IJER (Indonesian Journal of Educational Research), 2022)
This study inquired about parental engagement (PE) in schooling focusing on secondary school students in Kwara State, Nigeria. The study also examined the existing differentials in parental engagements based on school type, geographical location and students’ academic level. To accomplish the objectives, descriptive research of a survey type of design was adopted. Multi-stage sampling procedure was utilized in selecting 1,296 students from 72 secondary schools. Questionnaire titled: “Parental Engagement Assessment Questionnaire” (PIAQ) was utilized as data collection instrument. Mean scores, standard deviation, t-test and analysis of variance (ANOVA) were statistical tools appropriately used in analysing the collected data. The key finding make known that, the general level of parental engagement in schooling among secondary school students in Kwara State was moderate (GM = 2.78), while level of PE differs based on school type (t-value = 4.121, p =.000), geographical distribution (F = 3.402, p = 0.001) and students’ academic level (F = 3.463, p = .001). The study concluded that, despite the moderate level of PE in secondary school students schooling, significant disparity exists based on school ownership, geographic/senatorial distribution and students academic level.